Monosynaptic Glutamatergic Activation of Locus Coeruleus and Other Lower Brainstem Noradrenergic Neurons by the C1 Cells in Mice - Holloway, Benjamin B. (Society for Neuroscience, 2013)
The C1 neurons, located in the rostral ventrolateral medulla (VLM), are activated by pain, hypotension, hypoglycemia, hypoxia, and infection, as well as by psychological stress. Prior work has highlighted the ability of these neurons to increase sympathetic tone, hence peripheral catecholamine release, probably via their direct excitatory projections to sympathetic preganglionic neurons. In this study, we use channelrhodopsin-2 (ChR2) optogenetics to test whether the C1 cells are also capable of broadly activating the brain's noradrenergic system. We selectively expressed ChR2(H134R) in rostral VLM catecholaminergic neurons by injecting Cre-dependent adeno-associated viral vectors into the brain of adult dopamine-β-hydroxylase (DβH)(Cre/0) mice. Most ChR2-expressing VLM neurons (75%) were immunoreactive for phenylethanolamine N-methyl transferease, thus were C1 cells, and most of the ChR2-positive axonal varicosities were immunoreactive for vesicular glutamate transporter-2 (78%). We produced light microscopic evidence that the axons of rostral VLM (RVLM) catecholaminergic neurons contact locus coeruleus, A1, and A2 noradrenergic neurons, and ultrastructural evidence that these contacts represent asymmetric synapses. Using optogenetics in tissue slices, we show that RVLM catecholaminergic neurons activate the locus coeruleus as well as A1 and A2 noradrenergic neurons monosynaptically by releasing glutamate. In conclusion, activation of RVLM catecholaminergic neurons, predominantly C1 cells, by somatic or psychological stresses has the potential to increase the firing of both peripheral and central noradrenergic neurons.